Versatile roles of brassinosteroid in plants in the context of its homoeostasis, signaling and crosstalks - Saini, Shivani; Sharma, Isha; Pati, Pratap Kumar (Frontiers in Plant Science, 2015)
Brassinosteroids are a class of steroidal plant hormones that play diverse roles in plant growth and developmental processes. Recently, the easy availability of biological resources, and development of new molecular tools and approaches have provided the required impetus for deeper understanding of the processes involved in brassinosteroids biosynthesis, transport, signaling and degradation pathways. From recent studies it is also evident that brassinosteroids interact with other phytohormones such as auxin, cytokinin, ethylene, gibberellin, jasmonic acid, abscisic acid, salicylic acid and polyamine in regulating wide range of physiological and developmental processes in plants. The inputs from these studies are now being linked to the versatile roles of brassinosteroids. The present review highlights the conceptual development with regard to BR homeostasis, signaling and its crosstalk with other phytohormones. This information will assist in developing predictive models to modulate various useful traits in plants and address current challenges in agriculture.